Analysis of Hand Hygiene Compliance and Official Personal Protective Equipment Compliance on the Incidence of Nosocomial Infection In Outpatient Karanganyar Regencyhospital to Support of Hospital Accreditation - Oktavy Budi Kusumawardani; Joko Kismanto; Iwan Setiawan Adji; Kristina Widyastuti; Nadya Puspita Adriana (P3M Universitas 'Aisyiyah Surakarta, 2023)
Background: A nosocomial infection is an infection acquired or acquired in a hospital related to the provision of health services in health care facilities, where caregiver behavior includes hand washing, the use of protective equipment, the handling of medical equipment, the disinfection of the action site, the prevention of care and treatment, wound closure, and waste management. Objective: To assess officers' compliance with hand hygiene and use of personal protective equipment on the incidence of nosocomial infections in outpatients at Karanganyar District Hospital in support of hospital accreditation. Methodology: This study uses a type of quantitative research. The sample technique used total sampling with a population of all outpatient employees at Karanganyar District Hospital. Result: Compliance with hand hygiene and adherence to the use of personal protective equipment by officers affected the incidence of nosocomial infections where the F count exceeded the F table (47.313 > 3.10). Meanwhile, partially, handwashing compliance and compliance with the use of personal protective equipment for officers had an effect on the incidence of nosocomial infections. Conclusion: Compliance with hand hygiene and adherence to the use of personal protective equipmen